1997
DOI: 10.1128/iai.65.8.3430-3437.1997
|View full text |Cite
|
Sign up to set email alerts
|

Development of two monoclonal antibodies against Plasmodium falciparum sporozoite surface protein 2 and mapping of B-cell epitopes

Abstract: The Plasmodium yoelii sporozoite surface protein 2 (PySSP2) is the target of protective cellular immunity. Cytotoxic T cells specific for the Plasmodium falciparum analog PfSSP2, also known as thrombospondin-related anonymous protein (TRAP), are induced in human volunteers immunized with irradiated sporozoites. PfSSP2 is an important candidate antigen for a multicomponent malaria vaccine. We generated and characterized three monoclonal antibodies (MAbs) specific for PfSSP2/TRAP. The MAbs PfSSP2.1 (immunoglobul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…To date, numerous studies have been conducted in different geographical regions on pfs25 polymorphism in natural isolates but showed limited or no polymorphism . Furthermore, it has been reported that in the midgut of mosquito vector, the use of monoclonal antibodies against the native pfs25 completely blocks the development of P. falciparum oocysts .…”
Section: Discussionmentioning
confidence: 99%
“…To date, numerous studies have been conducted in different geographical regions on pfs25 polymorphism in natural isolates but showed limited or no polymorphism . Furthermore, it has been reported that in the midgut of mosquito vector, the use of monoclonal antibodies against the native pfs25 completely blocks the development of P. falciparum oocysts .…”
Section: Discussionmentioning
confidence: 99%
“…These peptide sequences are conserved; only the 3271 peptide T residue 161 shows genetic variability (11). Part of the sequence of 3279 ( 201 FLVG CHPSDGK GNLY 215 ) has been reported as being a B epitope (underlined), recognized by sera from malaria immune humans living in endemic areas (12). However, this epitope is not recognized by sera from Balb/C mice inoculated with the Pf SSP2 (vP1155) recombinant protein (12).…”
Section: Discussionmentioning
confidence: 99%
“…Part of the sequence of 3279 ( 201 FLVG CHPSDGK GNLY 215 ) has been reported as being a B epitope (underlined), recognized by sera from malaria immune humans living in endemic areas (12). However, this epitope is not recognized by sera from Balb/C mice inoculated with the Pf SSP2 (vP1155) recombinant protein (12). In contrast, mice immunized with multiple antigen peptides (MAPs) containing this epitope generate antibodies partially inhibiting in vitro sporozoite invasion of Hep G2 cells (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations